Natural Food Preservation Based on Randu Leaf Extract (Ceiba pentadra) and White Onion (Allium sativum) Extract on The Intensity of Bacterial Series In Tomato and Bakso Beef - Hidayat, Muhammad Syarif; Iswari, Retno Sri; Bintari, Siti Harnina (Proceeding International Conference on Science and Engineering, 2020)
The purpose of this study was to determine the effect of kapok leaf extract and garlic extract tubers effectively inhibit bacteria in tomatoes and beef meatballs. The research design uses a completely randomized design (CRD) which consists of one factor, namely food preservatives. Tomato and beef meatballs samples were immersed in kapok leaf extract and garlic bulb extract with different concentrations, namely 0, 50% and 50%, 100% garlic bulb extract and 100% kapok leaf extract for 15 minutes. Then the samples were stored at room temperature ranging from 22-31 degrees centigrade for 5 days. The results showed that the kapok leaf extract and garlic tuber extract effectively inhibited inhibiting bacteria.